Emulsification and demulsification of water-in-crude oil emulsion via microwave-assisted chemical treatment - Rasha, Mohammed Abd (2015)
Formation of emulsions during oil production and processing is a costly problem, both in term of chemicals used and production losses. The traditional ways of breaking emulsion using heat and chemicals are disadvantageous from both economic and environmental prospective. In this thesis, a new natural demulsifier knowing as “Cocamine MEA” in addition to an alternative energy potentials of microwave-assisted chemical approach were utilized and investigated in the demulsification of water-in-crude oil emulsion. Two types of crude oils were used, namely; crude oils A, and B. The study begun with some characterization studies to provide understanding of fundamental issues such as formation and characterization of the emulsion upon which further development on demulsification process could be achieved. The aim was to evaluate the performance of the new natural demulsifier compare with the existing demulsfiers as well as to obtain an optimized operating conditions of the demulsification process. For the stability performance test, three non-ionic emulsifiers were used, namely; Triton X-100, Span 80, and Cocamide DEA. Among these emulsifiers, Span 80 and Cocamide DEA permit the highest stability for the prepared emulsion. For the chemical demulsification performance test, six emulsifiers having different properties were utilized, namely: Octylamine, Hexylamine, Dioctylamine, Cocamine MEA, Polyethylene Glycol (PEG 600), and Polyethylene Glycol (PEG 1000). Among these demulsifiers, Octylamine was found to be the best in separating water and oil phases (90-100%) followed by Hexylamine (80-90%) for emulsion based on Span 80 at different phase ratios, respectively. Meanwhile, Cocamine MEA at the dose of 1 vol.% was found to be the best in separating water and oil phases (90-100%) followed by Octylamine and Hexylamine (90-100 %) at the dose of 1.5 vol.% for emulsion based on Cocamide DEA at different phase ratios. However, Dioctylamine, PEG 1000, and PEG 600 promote the monophase separation in separating the emulsion. Optimization of the microwave-assisted chemical demulsification using Face Centered Central Composite Design (FCCCD) under Response Surface Methodology found that Octylamine (1.5 vol.%) promotes a superior effect on demulsification rate of different types of emulsion, the exposure time (0.5-8) minutes and the MW power (270-360) watt were the most significant factors at different types of emulsion that consist with lower demulsifier utility, crude oil A emulsions needed higher MW power to separate the two phases. Based on the optimum conditions, the demulsification rate was accelerated by achieving a complete water separation for most types of emulsions. Characterizing the microwave generation and absorption at the optimum conditions showed that the w/o emulsion heated uniformly and deeply by long microwaves with less energy consumption. Results obtained in this thesis have exposed the potential application of Cocamine MEA as a natural composite for demulsification the water-in-crude oil emulsion. Moreover, results proved the capability of microwave-assisted chemical technology in developing the demulsification of w/o emulsions. Further works are nevertheless required to provide a deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry